2017
DOI: 10.1371/journal.pone.0173290
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial use in paediatric patients in a teaching hospital in Ethiopia

Abstract: BackgroundAntibiotics use in in children are different from adults due to a lack of data on pharmacokinetics, pharmacodynamics, efficacy and safety of drugs, different physiological spectrum, pediatrics populations being vulnerable to the majority of the illnesses, and the adverse effect of their irrational use is more serious. However, antibiotic use is not explored much in a paediatric population. The current study focused on antibiotic use among pediatric population using data from a tertiary hospital in Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 19 publications
(16 reference statements)
4
32
1
1
Order By: Relevance
“…In this study, it was also found that most of the patients were males. This is in concordance with the studies that were done in Guyana, India, Sierra Leone, Ethiopia, Cameroon [5,[22][23][24][25]. This similarity in findings suggests that male children are more likely to get infections than female children.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, it was also found that most of the patients were males. This is in concordance with the studies that were done in Guyana, India, Sierra Leone, Ethiopia, Cameroon [5,[22][23][24][25]. This similarity in findings suggests that male children are more likely to get infections than female children.…”
Section: Discussionsupporting
confidence: 91%
“…This is even though most bacteria are resistant against penicillins [36]. These findings are in agreement with what was found in studies that were done in Ethiopia, Cameroon, Nigeria, and Iraq [24,29,36,37]. These similarities in the findings could be due to the availability of these drugs in these various hospitals and hence their use.…”
Section: Discussionsupporting
confidence: 90%
“…In a study done in Ethiopia, it has been reported that penicillin G crystalline was the most (20%) frequently prescribed, followed by gentamicin (19%) and ampicillin, whereas in the present study cefpodoxime followed by azithromycin and amoxicillin-clavulanic acid were the commonest. 5 In another study done in the west, the most frequently used antibiotics were cephalosporins (43.7% of treated children), followed by macrolides, a combination of penicillins plus a beta lactamase inhibitors and broadspectrum penicillins (40.1%, 29.8% and 29.4%, respectively). Cephalosporins were frequently prescribed in the youngest children and macrolides were mostly prescribed in children >6 years of age.…”
Section: Discussionmentioning
confidence: 97%
“…Participants viewed antibiotic resistance to a lesser extent as a problem in their practice and in their health facilities, when compared to nationally, globally or generally. This could be explained by the limited awareness of the local antibiotic resistance patterns in their respective health facilities, either due to the limited use of microbiology laboratory to guide antibiotic therapy 30,31 or due to other factors such as limited microbiology services or lack of trust on the provided results. 26 A study from developed countries also showed similar findings, as health practitioners reported having a limited knowledge of the local resistance patterns and viewed antibiotic resistance to be less of a problem locally than nationally.…”
Section: Discussionmentioning
confidence: 99%